What is Epistemological Anarchism? - Kilian, Krzysztof J. (Filozoficzne Aspekty Genezy, 2024)
Epistemological anarchism is a methodological fallibilism, i.e. an approach according to which all scientific knowledge is not only provisional, but so are the methods of acquiring it. It is a belief that we are doomed to a provisional character of knowledge, yet the guide to this provisionality is a selected methodology. This conviction is contrasted with the belief that not only are we doomed to a provisional character of knowledge, but that we have no permanent guide to this provisional knowledge.